Tech Self-Efficacy, Innovation, and Performance: A Systematic Review Using the CIMO Framework - Syarifah Novieyana (Information Technology and Science (ITScience), 2025)
This systematic literature review (SLR) analyzes the strategic role of tech self-efficacy as a driver of innovation and organizational performance in various multidisciplinary contexts. Applying the PRISMA protocol, 144 articles were identified from the Scopus database and supplementary sources, and 32 studies met the final inclusion criteria (2020–2025). Using the CIMO (Context-Intervention-Mechanism-Outcome) framework, this review synthesizes empirical findings from the fields of education, technology, entrepreneurship, and workplace inclusion. The results indicate that tech self-efficacy consistently improves innovative behavior, technology adoption, creativity, and organizational performance, mediated by organizational support, inclusive leadership, digital readiness, and trust in AI. Methodological trends are dominated by quantitative approaches, particularly Structural Equation Modeling, while qualitative and mixed methods studies are still limited. Geographically, publications are dominated by China, creating a gap in cross-cultural representation, particularly in Africa and Latin America. Theoretically, research still relies on Social Cognitive Theory, Technology Acceptance Model, and Diffusion of Innovation. Despite the rapidly growing literature, it demonstrates conceptual fragmentation, a lack of integration of cultural and temporal dynamics, and limited discussion of the digital divide and psychological well-being in technology-based workplaces. This SLR provides a more holistic conceptual understanding of tech self-efficacy and offers a multidimensional framework for future research. Recommendations include expanding cross-cultural studies, utilizing mixed methods , and exploring new topics such as AI self-efficacy, digital resilience, and inclusive innovation ecosystems.